An appreciative inquiry to identify the continuing education needs of Aboriginal and Torres Strait Islander health practitioners in regional Queensland - Martyn, Julie-Anne; Woolcock, Ann (The Australian Journal of Indigenous Education, 2020)
Abstract Aboriginal and Torres Strait Islander health practitioners (Practitioners) have a broad scope of practice and play a pivotal role in addressing health disparities for Aboriginal and Torres Strait Islander people. Practitioners are required to maintain knowledge and skill levels to provide ongoing quality care. However, continuing education (CE) opportunities for Practitioners in regional areas are limited and little is known about the types of CE best suited to Practitioners. This study aimed to identify the CE needs of Practitioners working in a South-East Queensland region in Australia. Participatory action research and appreciative inquiry were combined in this multi-staged study. A local Aboriginal and Torres Strait Islander advisory group provided cultural guidance for the study design and implementation. Supervisors and Practitioners from two Aboriginal Medical Services consented to participate. In stage one of this study, the supervisors were interviewed and the Practitioners contributed to focus groups. The Practitioners prioritised their CE needs in the second study stage using a questionnaire. The participants identified Practitioner CE needs and group 2 listed their career aspirations and the best practitioners were described as ‘Deadly’. The Deadly practitioner had diverse practice knowledge, skills and attributes. The Practitioners had career aspirations beyond their role and a desire to learn. However, their career advancement was stifled by a lack of CE opportunities. CE in regional areas is limited. Practitioners are disadvantaged by exclusion. Enhancing CE opportunities for Practitioners will positively impact the health of regional Aboriginal and Torres Strait Islander communities by building social capital. Therefore, future research on Practitioner roles and CE is needed.